HISTORY OF NATIONAL ECONOMIC SYSTEM FORMATION IN THE REPUBLIC OF SOUTH AFRICA - N. S. Zagrebelnaya; V. N. Shitov (Vestnik MGIMO-Universiteta)
The article analyses specific historic features of formation of agrarian and industrial sectors of Republic of South Africa since the establishment of Cape Colony. These features resulted from much earlier colonization of South Africa in comparison with other Sub-Saharan African countries on the one hand and from a large-scale influx of Europeans to the South Africa on the other hand. The two most important of these specific features are the following. First. Contrary to other countries of Sub-Saharan Africa development of the agrarian sector of Republic of South Africa was based on private property and western technologies from the start. Second. The sector is not divided into «African» and «European» sub-sectors, and South-African agricultural produce has always been oriented to both: external and internal markets. Development of industrial sector of Republic of South Africa started with creation of extractive industries, namely: extraction of diamonds and of gold. The authors specifically emphasize the role of gold extraction which grace to its effect of multiplicator opened the way for industrial revolution in the South of Africa. Development of manufacturing was mainly based on import-substitution. The article argues that there were several stages of import-substitution and analyses their outcomes. The authors point out to the special importance of import-substitution during the period of I World War and II World War.